PERCEIVE USEFULNESS IN USING GOOGLE FORM IN THE LEARNING ENGLISH - Yosua Anang; Ayu Istiana Sari (English Education Department Slamet Riyadi University Surakarta, 2023)
The aims of the research were: to analyze perceived usefulness in using Google Form in the learning English. This study was descriptive qualitative research. In collecting the data, the researcher used questionnaire to student and interview to teacher. To collect the data of the questionnaire the researcher used the table questionnaire by Google Form. The researcher used Source triangulation, Triangulation technique and Time triangulation to check validation. The result of the research the result of the research, it can be concluded that from several questionnaires using Google Form in learning English can help the student, the learning more interesting, can save time, save energy, and enhance the students’ English skills. But the other side using Google Form in learning English waste of cost and it needs stable internet connection. Key Words : Students Acceptance, Google Form, Online Learning, Learning English